Interactive Multimedia Development in The Learning Process of Indonesian Culture Introduction Theme for 5-6 Year Old Children - Maria, Ulfa; Rusilowati, Ani; Hardyanto, Wahyu (Universitas Negeri Semarang, 2019)
Due to the sore concern of young generation’s insight about Indonesian cultures, thereby it is crucial to introduce them since the early ages. Common ways of introducing Indonesian cultures were by means of pictures, which made the children easily lost their interest. This research was aimed to design interactive multimedia learning in introducing Indonesian cultures especially for early children and also to learn about the effectiveness of interactive multimedia implementation during the classroom learning process. The research is a Research and Development research. Data collection methods were: observation, interview, documentation, and student worksheet test. Data analysis was included: designing interactive multimedia of Adobe Flash CS4, and descriptive analysis of percentage and effectiveness test. The research results show that: the design of learning multimedia for Indonesian culture theme in form of interactive game, the implementation of interactive multimedia that resulted in increasing effective class learning process, presented by the scoring result of pre-test in average of 2.07 to 2.73 for the post-test with mastery of learning result amounted to 80%. Interactive multimedia employed in learning process has given a new variation for the students, in which it was easier for them to memorize the content of the learning subject when they were shown with certain interesting pictures and sounds. Multimedia was able to help the development of interactive responses during the learning process. This result highly expects could be useful in developing and enhancing the scientific knowledge in the area of early childhood education aided by interactive multimedia.